Caffeine, surfactants and organic matter in a high Andean River: Chumbao River case, Apurimac, Peru - David Choque-Quispe; Ruth Karina Herbas-De la Cruz; Carlos A. Ligarda-Samanez; Aydeé M. Solano-Reynoso; Dianeth Buleje-Campos; Yudith Choque-Quispe; Jenny C. Muñoz-Saenz; Zaida Olinda Pumacayo-Sanchez; Liliana Asunción Sumarriva-Bustinza; Nikol Alexsandra Silvera Ticona (Case Studies in Chemical and Environmental Engineering, 2024)
Discharge of domestic, industrial, and commercial wastewater into water bodies, exposes the population to emerging contaminants, such as caffeine and surfactants, which, when present in small quantities, cause changes in the physicochemical parameters of the water. The research aimed to evaluate the level of caffeine, organic matter, and anionic surfactants in the water of the micro-basin of the Chumbao River, Andahuaylas, Apurimac. Sampling was carried out during low water and flood periods, and the physicochemical characteristics of the water were evaluated. The results were compared, with the environmental regulations for Peruvian water bodies, which showed that pH, water color, nitrite, COD, DO, BOD5, and total phosphorus exceeded the levels established in the ECA-Peru. Likewise, the analysis according to the degree of biodegradability indicated that the waters of the Chumbao River are biodegradable and not very contaminated for the most part. The maximum surfactant concentration was 1.01 mg/L in both study seasons. As for caffeine, it presented maximum value of 52.22 μg/L during the dry season. The physicochemical properties analyzed were influenced by wastewater dischargers from different origins, with caffeine and surfactants being the indicators of contamination from anthropogenic sources.